AI dan Agama: Tantangan dan Peluang dalam Era Digital - Sehat Ihsan Shadiqin; Tuti Marjan Fuadi; Siti Ikramatoun (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
This article addresses the challenges and opportunities arising from the interaction between Artificial Intelligence (AI) and religion in the digital era. Concurrently with the advancement of technology, AI has demonstrated its capability to access and analyze an extensive array of data, encompassing religious texts among others. This phenomenon introduces new prospects for the interpretation and comprehension of religious texts, previously confined to the purview of theologians and scholars but now rendered accessible to a broader spectrum of individuals. Nevertheless, this development also engenders a constellation of challenges. The present article endeavors to elucidate the manner in which religion can acclimate itself to the progressively augmenting role of AI within our society. The foremost challenges that confront religion in this digital epoch shall be expounded upon. Moreover, an examination of how religion can harness this technology for its own purposes will be undertaken. Furthermore, an inquiry into the ethical boundaries governing the role of technology within the realm of religion will be conducted. With a focal point on these inquiries, the article seeks to furnish a comprehensive delineation of the role of AI in the religiosity of the future.Artikel ini membahas tantangan dan peluang yang muncul dari interaksi antara kecerdasan buatan (AI) dan agama dalam era digital. Seiring dengan semakin canggihnya teknologi, AI telah mampu mengakses dan menganalisis data yang sangat luas, termasuk teks-teks keagamaan. Hal ini di satu sisi memberikan kemungkinan baru untuk interpretasi dan pemahaman teks agama, yang sebelumnya menjadi wilayah eksklusif para teolog dan ulama, sekarang dapat dilakukan oleh siapa saja. Meskipun demikian, hal ini juga menimbulkan sejumlah tantangan. Artikel ini akan menjelaskan bagaimana agama dapat beradaptasi dengan peran AI yang semakin meningkat dalam masyarakat kita. Apa tantangan terbesar yang dihadapi oleh agama di era digital ini? Bagaimana agama bisa memanfaatkan teknologi ini untuk tujuan mereka sendiri? Dan apakah ada batas etika bagi peran teknologi dalam agama? Dengan berfokus pada pertanyaan-pertanyaan ini, artikel ini berusaha untuk memberikan gambaran komprehensif tentang peran AI dalam agama masa depan.Â